The Effect of Motivation on Employee Performance in Biological Product Division of PT Medion Bandung Barat - Hamali, Arif Yusuf; Khodijah, Ai Siti; Febriyanti, Ine (Journal the Winners: Economics, Business, Management, and Information System Journal, 2015)
This research was conducted at Biological Product Division of PT Medion Bandung Barat, aimed to determine correlation of motivation and employee performance, and also to analyze the effect of motivation on employee performance at Biological Product Division of PT Medion Bandung Barat. Respondents of this research were 45 people, selected with simple random sampling technique. The methods used were descriptive and associative, which tested the connection using the Spearman rank correlation analysis, and to determine the accuracy of measurement using the validity and reliability test. Results of the validity and reliability test of variables X and Y are valid and reliable. Calculations were performed using SPSS software version 19. The result of this study showed that motivation is in the category of good and employee performance is also in the category of good. Results showed the correlation of motivation with employee performance at Biological Product Division of PT Medion Bandung Barat with correlation coefficient of 0,568. Based on the criteria champion, this relationship is in the criteria of strong enough relationship. Results of this calculation showed the coefficient of determination is 32, 26%. It is showed that the hypothesis is proved that there is an influence of motivation to employee performance at Biological Product Division of PT Medion Bandung Barat.